Teaching English for Student Flourishing - Sugiono Sugiono (Universitas Nurul Jadid, 2023)
Teaching for student flourishing is part of social justice education, which highlights positive changes in society through education. It opens a space for teachers, English language teachers in particular, to accommodate different backgrounds and characteristics of students, from which it gives them opportunities to flourish. However, teaching within this perspective is not that easy. The English teachers face a number of problematic challenges during the teaching learning activities. They need to find the ways to overcome these challenges. This paper aims to determine the challenges faced by the English teachers and gives some insights on how to surmount the problems. It employs a qualitative study, and argues that the English teachers have some challenges in teaching English for a flourishing life of students. They need to concern identifying the challenges and figure out the ways to solve it.